Urban agriculture in Portugal: from spontaneity to the institutionalization of urban gardens - Hespanhol, Rosangela Medeiros [UNESP] (Revues Org, 2019)
Urban agriculture came to stand out in the world scenario in the last years of the twentieth century and beginning of the XXI, due to the greater concern of the population with food security and the aggravation of social, economic and environmental problems in the cities. In the European context, urban agriculture is not a recent phenomenon, however, the way it is managed by the public power has presented significant changes, since this activity tends to be increasingly integrated with urban management and land use planning policies. This is the case of urban vegetable gardens in Portugal, analyzed in this article. It has been verified, through the field research, that there are vegetable gardens that appeared spontaneously and the public power does not exercise control or inspection on the same ones and there are gardens organized by the public power. The economic crisis and its social effects, coupled with growing concern about the origin of food consumed, have led to the expansion of urban gardens, which present a diversity of forms of organization, production systems and objectives. It was verified, through interviews, that urban agriculture has provided the production of food for subsistence, without the use of pesticides; the constitution of spaces of intergenerational and intercultural coexistence; the search for greater social cohesion through the exchange of experiences among the participants; and the promotion of environmental education, which also emphasized the social and cultural importance of these cultivation practices in the city.
Keywords: Urban agriculture; Rural-urban migration; Economic crisis; Urban gardens; Portugal